Effect of Oral Administration of Selenium and Vitamin E on the Quality of Fresh, Refrigerated and Frozen Semen in French Bulldog Breed Dogs - Mungai Chacur, Marcelo George; Ripari de Souza, Mariana Grandis; Souza, Camila Dutra de; Cremasco, Camila Pires [UNESP] (Univ Fed Rio Grande Do Sul, 2017)
Background: New methodologies have been developed seeking to maximize pregnancy rate in female dogs created in commercial kennels, and also in order to maintain the quality of canine semen after dilution, refrigeration or freezing. One of the main factors that generate damage to sperm is oxidative stress, to minimize sperm damage, selenium and antioxidants like vitamin E are administered, by oral administration, seeking to improve the quality of semen. The objective was to study the effect of vitamin E and selenium, by oral administration, in the quality of fresh, refrigerated and frozen semen in adult dogs French Bulldog breed. Materials, Methods & Results: Semen samples were collected from 5 adult dogs, French Bulldog breed, being 2 semen drawing before the daily oral supplementation with vitamin E and selenium (ESE (R)) and semen drawing at 20, 40 and 60 days after the beginning of oral supplement. The ejaculated samples were diluted in TRIS - fructose citric acid (3.28 g TRIS-hydroxy-methyl-amino-methane, 1.78 g of citric acid monohydrate and 1.25 g of D - fructose, dissolved in 100 mL of distilled water and added of 20% egg yolk and 6% of glycerol. The characteristics evaluated in fresh semen were: volume (mL), color, appearance, concentration (x106/mL), sperm motility (%), sperm strength (1 to 5) and morphology (%). For refrigerated and frozen semen were analyzed: sperm motility (%), sperm strength (1-5) and morphology (%). Diluted semen samples were centrifuged at: 1500 g/10 min and pellets formed by sperm of each ejaculated, detached from the tube wall were diluted homogeneously in the diluent TRIS type up to the final volume of 1.5 mL. After that, packaged in 0.5 mL French straws, kept under refrigeration at 5 degrees C/4 h, placed in nitrogen vapor at -120 degrees C/15 min, and dipped in liquid nitrogen at -196 degrees C and then stored on identified rachis and stored in liquid nitrogen container until the time of thawing in water bath at 37 degrees C/30 s for semen microscopic analysis. Data from fresh, refrigerated and frozen semen were statistically analyzed by analysis of variance and the average compared by 5% of Tukey test. Fresh semen sperm concentration differed (P < 0.05) between the samples, rising after 40 days after the beginning of oral supplementation with selenium and vitamin E. For the spermatic strength, better score (P < 0.05) was observed at collection 4, in 40 days after the beginning of oral supplementation to dogs. For fresh and refrigerated semen, the total defects, defects of head, acrosome and tail did not differ (P > 0.05) between the samples. Total sperm defects and minor head and tail defects did not differ (P > 0.05) between the samples in post-thawing. Regarding the acrosome defects after thawing, there was a significant reduction (P < 0.05) in samples performed 40 and 60 days after the beginning of oral supplementation with selenium and vitamin E. Discussion: Attention should be paid for what purpose the extenders within the refrigeration or freezing biotech will be used. The managed supplement, by oral administration, containing selenium and vitamin E, influenced beneficially raising the sperm concentration in fresh semen and decreasing the acrosome defects in frozen semen. Oral administration of supplementation with selenium and vitamin E is recommended for improving the quality of fresh and frozen semen in dogs.
Keywords: dogs; nutritional supplement; antioxidant; frozen semen; semen analysis